Buffered accelerated weathering of limestone for storing CO2: Chemical background. (December 2021) - Caserini, Stefano; Cappello, Giovanni; Righi, Davide; Raos, Guido; Campo, Francesco; De Marco, Serena; Renforth, Phil; Varliero, Selene; Grosso, Mario
Highlights: A method to store permanently CO2 in seawater in form of bicarbonates is discussed. The method is an evolution of the Accelerated Weathering of Limestone (AWL). Ca(OH)2 is added to buffer the unreacted CO2 before the discharge in seawater. BAWL overcomes the main limitations of AWL and buffers ocean acidification. A preliminary storage cost is 100 € per tonne of CO2 coming from an external source. Abstract: We present an evolution of the Accelerated Weathering of Limestone (AWL) method to store CO2 in seawater in the form of bicarbonates. Buffered Accelerated Weathering of Limestone (BAWL) is designed to produce a buffered ionic solution, at seawater pH, which derives from the reaction between a CO2 stream and a powder of micron-sized calcium carbonate particles in a long tubular reactor. Addition of calcium hydroxide to buffer the unreacted CO2 before the discharge in seawater is also provided. BAWL aims to overcome the main limitations of AWL, such as the high amount of water needed, the large size of the reactor, the risk of CO2 degassing back into the atmosphere, if the ionic solution is released into shallow waters, as well as the induced seawater acidification. This paper presents the chemical background of the technology and evaluates its feasibility by considering the chemical equilibria in the different phases of the process. The CO2 emitted for limestone calcination leads to a 24% CO2 penalty; a preliminary cost analysis assesses a storage cost of 100 € per tonne of CO2 from an external source. It finally discusses the main features to be considered for the design at the industrial scale.